Are There Any True Moral Enhancements?: Aristotelian and Thomistic Perspectives - Rath, Beth A. (Philosophy, theology and the sciences, 2023)
Questions about moral enhancements have arisen within the context of transhumanism. One of the most fundamental of these questions is whether true moral enhancements are even possible. My paper aims to address this question with a 'yes' and 'no' reply. After laying out criteria for what counts as moral enhancements, I look at whether it is possible to make a person morally better within the context of two distinct virtue-ethics frameworks, namely, Aristotle's and Thomas Aquinas's. I argue that, on Aristotle's account, no biotechnological moral enhancement can directly make someone morally virtuous, although virtue may be enhanced indirectly. For Aquinas, the same argument holds, but I show that, on his view, grace counts as the only true moral enhancement.